Radio messaging on good agricultural practices in Côte d'Ivoire - CGIAR Research Program on Rice (2019)
Radio messaging on good agricultural practices in rice was broadcasted for 90 days (twice a day) from Radio RTI in Bouake. We received feedback from farmers and other stakeholders and input dealers' feedback about radio messaging for further improvement.